Contrasting PCB bioaccumulation patterns among Lake Huron lake trout reflect basin‐specific ecology. (24th November 2015) - Paterson, Gordon; Ryder, Mark; Drouillard, Ken G.; Haffner, G. Douglas
Abstract: This study collected multiple age classes of lake trout from Lake Huron's Main Basin, Georgian Bay, and North Channel regions to compare and contrast top predator polychlorinated biphenyl (PCB) bioaccumulation patterns in separate compartments of the same ecosystem. Sum PCB concentrations were highest for Main Basin (260 ± 24.9 ng g −1 wet wt) fish, followed by Georgian Bay (74.6 ± 16.2 ng g −1 ) and North Channel (42.0 ± 3.3 ng g −1 ) fish. Discriminant functions analysis of lake trout PCB profiles and stable carbon (δ 13 C) and nitrogen (δ 15 N) isotope values clearly distinguished fish by location, indicating high degrees of basin fidelity throughout their lifetimes in addition to highly contrasting PCB bioaccumulation profiles. These unique profiles were not attributable to significant differences in lake trout lipid contents ( p = 0.856) or trophic position (δ 15 N; p = 0.334), with rainbow smelt representing the primary prey across the basins. Furthermore, significant differences were observed among the basins for the relationships between PCB biomagnification factors and hydrophobicity. An empirical model for predicting PCB biomagnification in Lake Huron lake trout indicated that basin‐specific population growth rates and prey abundances were significant for explaining these contrasting patterns of PCB bioaccumulation. The results of the present study are fundamental for understanding the role of ecology in legacy persistent organic pollutant (POP) bioaccumulation. Specifically, ecosystem characteristics such as prey abundances, foraging ecology, and ultimately consumer growth can regulate the variability of legacy POP bioaccumulation as observed within and among a wide range of freshwater ecosystems. Environ Toxicol Chem 2016;35:65–73. © 2015 SETAC